Batch recall of French plasma‐derived products due to variant Creutzfeldt‐Jakob disease risk: the psychological impact on haemophilic patients, changes in their therapeutic demands and behaviour and ethical considerations. (January 2015) - Aouba, A.; Harroche, A.; Frenzel, L.; Torchet, M. ‐F.; Rothschild, C.; François, I.; Mamzer‐Bruneel, M. ‐F.
Summary The choice of plasma‐derived products (PdP) vs. recombinant products (RP) for treating haemophilia is influenced by the infectious and perceived safety of the products. Batch recall of PdP due to the risk of variant Creutzfeldt‐Jakob disease (vCJD) may have unfavourable psychological impacts on haemophilia patients and influence their product preferences. This study aimed to assess the psychological impact of batch recalls of PdP in six haemophilia patients and their therapeutic demands, and to discuss the ethical problems in physicians' management of this event. A survey was conducted using a new interview form and an existing anxiety and depression questionnaire. Batch recalls produce recurrent negative emotional outcomes in haemophiliacs and their families. The quality, understanding and efficiency of the batch recall announcements were unsatisfactory in some respects. Only one patient still had some of the vials in question, and only three patients understood the real reason for the batch recall. Four patients asked to change their PdP for RP; a fifth patient was considering doing so. Here, topics for discussion include the delivery of an unclear message to patients about a very uncertain risk of a frightening disease, the reasons to maintain PdP when RP are largely available, except in specific cases, and the related discomfort for caregivers. The ethical questions revealed by batch recalls and the high psychological impact of vCJD risk on patients can no longer be ignored, and require surveys assessing the rationales and choices of the healthcare authorities, manufacturers, prescribers and users.